Rhinofacial Basidiobolus Misdiagnosed as Granulomatosis with Polyangiitis - Hussain, Aneela; Ilyas, Aisha; Jabeen, Kausar; Mahmood, Syed Faisal (Infectious Diseases Journal of Pakistan, 2022)
We report a case of a young female, initially misdiagnosed as Granulomatosis with Polyangitis (Wegener’s). Repeat histopathology and culture however revealed Basidiobolus species. She was managed successfully with antifungals, highlighting the need for a high index of suspicion for molds in unusual presentations. Key Words: Basidiobolus; Granulomatosis with polyangiitis